TINJAUAN YURIDIS TERHADAP PERALIHAN PERUNTUKAN TANAH WAKAF DI KOTA TASIKMALAYA DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF - Syaira Anabila; Apip Nur; Rika Maryam (Jurnal Penelitian Hukum Galunggung, 2025)
This study discusses the transfer of waqf land in Tasikmalaya City from the perspective of Law No. 41 of 2004 concerning Waqf. The law stipulates that waqf property is permanent and may not be transferred except through the istibdal mechanism under strict procedures. However, in practice, several cases of waqf land transfer were found to be inconsistent with the provisions, such as changes of status into grants or even sales without approval from the Minister of Religious Affairs and the Indonesian Waqf Board (BWI). This study examines: (1) how the designation of waqf land is regulated under Law No. 41 of 2004 concerning Waqf, and (2) how the process of waqf land transfer occurs. The purpose of this study is to determine the regulation of waqf land designation under Law No. 41 of 2004 and to analyze the process of waqf land transfer in Tasikmalaya City. The theories used include the theory of utility, the theory of legal effectiveness, and the theory of waqf. This research employs a juridical-empirical approach with a qualitative method through interviews. The results show that: (1) the designation of waqf land may not be changed except for public interest purposes in accordance with the general spatial plan (RUTR), based on applicable laws and regulations, and not contrary to Sharia. Such transfer may only be carried out after obtaining written permission from the Minister with the approval of the Indonesian Waqf Board and must be exchanged with property of equal or greater benefit and value. (2) The transfer process that occurred in Tasikmalaya did not comply with the provisions of Law No. 41 of 2004 concerning Waqf, as the requirements for public interest in line with the spatial plan (RUTR) were not met, written approval from the Minister and BWI was not obtained, and the exchange value was not equivalent to the original waqf property.